HOW DO STUDENTS FACE ENGLISH SPEAKING DIFFICULTIES AT A COASTAL REGENCY OF NATUNA: A CASE STUDY AT AN ISLAMIC STATE SENIOR HIGH SCHOOL - Iswanto, Joko; Nurfadilah, Syarifah (GoAcademica CRP, 2024)
This research describes the analysis of student difficulties in English speaking skills faced by 10th Grade students of MAN 1 Natuna in the 2021/2022 academic year. This research used qualitative research methods. The researcher chose class X IPA 1 as the object with a total of 27 students. In collecting the data, researcher used observations, and interview. From the data analysis, the researcher found some conclusion The problem of students in mastering speaking skills is that students have limited vocabulary, they confused to pronounce words in English, lack grammar, cannot speak fluently, and have difficulty understanding what the speaker is saying. In addition, students inhibit to practice speaking English and usually use their mother tongue. The cause of students having difficulty in mastering speaking skills refers to the learning objectives, it can be concluded that students have psychological factors such as lack of confidence, fear of being wrong, anxiety, shame and lack of motivation that hinders them in practicing speaking in English. These factors, such as fear of making mistakes, are generally caused by their fear of being laughed at by their friends.